Practiceopolis: Journeys through the contemporary architectural profession - Megahed, Yasser; Sharr, Adam; Farmer, Graham (Interstices: Journal of Architecture and Related Arts, 2016)
Supervisors: Adam Sharr, Graham FarmerThe contemporary architectural profession is dominated by a technical-rational culture of practice. The term refers to commercially-driven practices that are often associated with the production of buildings by or for multinational corporations and tend to echo their values. This research interrogates the imperatives of this domination on the original values of the architectural profession. It builds upon two premises: firstly; mapping different cultures of practice constituting the contemporary understanding of the profession; secondly, questioning the increasing closeness between the values of the architectural profession and the instrumentalist values of other actors in the building industry. To do so, the research introduces the imaginary city of Practiceopolis as a methodological device that allows the modelling of contemporary cultures of practice and dramatises their dialogues. The research ends with propositions regarding the particular values of the architectural profession and proposes a critical-instrumental mindset to explore how these values could be defined, communicated, and marketed.